A Case of Cerebral Granuloma and Optic Papillitis due to Brucella sp. - A. Chiappe-Gonzalez; A Solano-Loza (Case Reports in Infectious Diseases)
We document a case of a 24-year-old woman who presented with cerebral granuloma and optic papillitis associated to Brucella sp. infection, whose diagnosis was made with a brain biopsy and serology tests, with clinical improvement following specific antibiotic therapy. The patient was followed up for over a year without evidence of relapse.